2010
DOI: 10.1186/1471-2288-10-12
|View full text |Cite
|
Sign up to set email alerts
|

The Manchester Color Wheel: development of a novel way of identifying color choice and its validation in healthy, anxious and depressed individuals

Abstract: BackgroundFor the purposes of our research programme we needed a simple, reliable and validated method for allowing choice of a color in response to a series of questions. On reviewing the literature no such instrument was available and this study aimed to rectify this situation. This was achieved by developing a simple method of presenting a series of colors to people validating it in healthy volunteers and in individuals where color choice might be distorted, namely anxiety and depression.MethodsA series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
72
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 30 publications
(31 reference statements)
5
72
1
Order By: Relevance
“…This hypersensitivity is not confined to the rectum [47], and there is now evidence that IBS patients react more to other external stimuli, such as sound [48][49][50], and the co-existence of fibromyalgia with IBS [51] is suggestive of a more generalized hypersensitivity, which also involves the central nervous system [52][53][54]. We have recently been studying the role of color and imagery in IBS in two ways [55,56]: firstly, by having a medical artist paint, in watercolor, the images which patients have of their illness [56] and secondly, by developing an instrument, called the Manchester Color Wheel [57], which enables individuals to choose a color in relation to a question such as ''color of mood?'' or ''color of illness?.''…”
Section: Introductionmentioning
confidence: 99%
“…This hypersensitivity is not confined to the rectum [47], and there is now evidence that IBS patients react more to other external stimuli, such as sound [48][49][50], and the co-existence of fibromyalgia with IBS [51] is suggestive of a more generalized hypersensitivity, which also involves the central nervous system [52][53][54]. We have recently been studying the role of color and imagery in IBS in two ways [55,56]: firstly, by having a medical artist paint, in watercolor, the images which patients have of their illness [56] and secondly, by developing an instrument, called the Manchester Color Wheel [57], which enables individuals to choose a color in relation to a question such as ''color of mood?'' or ''color of illness?.''…”
Section: Introductionmentioning
confidence: 99%
“…Many instruments have been developed, such as the Pfister's Colour Pyramid test (1950) (Schaie, 1963); the Rorschach Inkblot test (1927) (Klopfer & Davidson, 1962), the Lüscher Colour test (1948) (Lüscher, 1969), the Lowenfeld Mosaic test (Lowenfeld, 1952); and different tests used regionally, for instance the Frieling Test (Muths, 2001), the Weyssenhoff test (Weyssenhoff, 1991) or, recently developed the Manchester Colour Wheel (Carruthers, Morris, Tarrier, Whorwell, 2010). They have been designed mostly to interpret the human psyche, for instance personality.…”
Section: Colours In Psychological Diagnosesmentioning
confidence: 99%
“…3,4 They have further elaborated this approach in studies of the Manchester colour wheel, where a relationship was found between emotions and mood state and choice of colours. [5][6][7] Colour choices were not associated with symptom severity but did change as associated mood disturbances changed. 6 We did not cite these studies as the aims of our study and its use of pictograms were very different.…”
mentioning
confidence: 91%